Collapsing health care in Serbia and Montenegro. - Black, M E (1993)
Serbia and Montenegro together form the Federal Republic of Yugoslavia. As well as the Serb majority this includes the mixed province of Vojvodina, the mainly Albanian population in Kosovo, and the large Muslim minority in Sandzak. Since the start of war in 1991 the attention and sympathies of the world have focused on Bosnia and Croatia. The United Nations imposed economic sanctions on the federal republic in 1992, although in theory medical supplies and aid are exempt. The economy has now collapsed under the triple burden of war, loss of trade between the republics, and UN sanctions. A major public health catastrophe is unfolding in the federal republic.